Morphology of Near- and Semispherical Melted Chips after the Grinding Processes Using Sol-Gel Abrasives Based on SEM-Imaging and Analysis - W. Kapłonek; K. Nadolny; W. Habrat (Advances in Materials Science and Engineering)
Selected issues related to SEM-imaging and image analysis of spherical melted chips formed during the grinding process are presented and discussed. The general characteristics of this specific group of machining products are given. Chip formation phenomena, as well as their overall morphology, are presented using selected examples of near- and semispherical melted chips occurring singly or concentrated in clusters on the grinding wheel surface after the machining process. Observation of the spherical melted chips and acquisition of their images were carried out for grinding wheel active surfaces with microcrystalline sintered corundum abrasive grains SG™ after the internal cylindrical grinding process of a 100Cr6 steel and Titanium Grade 2® alloy by use of a scanning electron microscope, JEOL JSM-5500LV. Analysis of the obtained SEM micrographs was carried out by Image-Pro® Plus 5.0 software to determine the selected geometrical parameters describing the morphological features of the assessed chips.